(untitled) (Medico Legal Update, 2020)
Background: Vitamin D has different biological actions in the body . Vitamin D has the pleiotropic effects in multiple organ systems. Vitamin D (vit D) deficiency has been found to have an inverse relationship with the occurrence of type-2 diabetes mellitus (DM). The aim of this study was to assess the vit D level in type-2 diabetic patients. Objective: To identify Vitamin D level and its correlate with type2 diabetes mellitus among old adults. Methodology: This was across sectional descriptive observational study included a non-probability (convenient sample) of elders (>65 years both women and men) in Hilla City, Babylon province, the period of the study started from the first of January through August 2019, the sample size was calculated according to the sample size calculation equation with 95% confidence level, 300 elderly people were participated voluntarily in this study after explaining the objective of the study by the researcher, the response rate in this study 100%. This study was approved by the Ethics Committee of College of nursing - University of Babylon, a pretested questionnaire was used to interview the participants after obtaining their verbal consents, the sample included old adults, apparently healthy & not receiving vitamin D supplement, serum level of Vitamin D that made by chemo immunoassay method (maglumi instrument). Data about demographic characteristics, drug uses, number of chronic diseases, as well as measurement of mean blood sugar of each participant were done single handy by the researcher. Blood sugar was measured using electronic system, blood sugar more than 170mg/dl considered diabetes in this study or those who diagnosed previously as diabetes (type 2) and taking anti diabetic drugs. Vitamin D levels are divided into three categories .deficient < 20ng/ml, insufficient between 23-29ng/ml and normal level 30-100 ng/ml 27 . Data were analyzed by using the (spss) package version 23. The chi-square test was used to test the associations between variables. The association considered statistically significant when the P-value is less than 0.05. Results: The study included 300 participants, most of the study sample had either insufficiency or deficiency of Vitamin D level. Diabetic elders in this study had significant low serum Vitamin D level (both deficiency and insufficiency of vitamin) as compared to healthy group, this difference was statistically significant p<0.05. Conclusion: There was a significant inverse relationship between vitamin D level and type 2 diabetes mellitus.